Microrganismos Associados à Cortiça em Diferentes Fases da sua Fileira (Silva Lusitana, 2005)
Several microorganisms have been considered responsible for decrease in cork quality and wine off - flavours. To improve the knowledge on cork microbiology throughout the tree to end product (stopper) steps, the work developed included two components. The first, on fungal populations colonising the tree, aims to evaluate the probable role of the tree as source of both slab and stopper contamination. The second focusing the collection of dispersed information about the microbial populations, throughout the industrial cork steps, has a main objective to constitute a basis for the delineation of further studies on this matter. The integration of results allows the following conclusions: (i) the microbial populations change throughout cork manufacture process, reflecting both the different environmental conditions and methods used; (ii) the persistence of a large part of these populations throughout the several phases (tree to end product), indicates that the tree is, probably one of the most important microorganism source; (iii) a fraction of these populations included in the group are pointed out as capable of producing secondary metabolites that affect both cork and wine quality; (iv) no significant differences between microbial population diversity and tree vigour level were found. The results obtained did not allow a relationship between decrease of tree vigour and wine-off flavours. Dispersed and sometimes inaccurate information makes it difficult to build a consistent knowledge frame, indicating that a well - balanced multidiscipline research program including all the partners involved in cork processing, is an urgent necessity.